The overexpression of Rabl3 is associated with pathogenesis and clinicopathologic variables in hepatocellular carcinoma - Yuhang Pan; Zhiyong Liu; Zhiying Feng; Dayang Hui; Xiangqi Huang; Dayue Tong; Yi Jin (Tumor Biology, 2017)
Overexpression of Rabl3 is associated with some malignancies. However, their relationship with hepatocellular carcinoma remains unclear. In this study, the expression of Rabl3 in hepatocellular carcinoma cell lines, and four pairs of matched hepatocellular carcinoma tissues and their adjacent normal hepatic tissues were detected by quantitative reverse transcription polymerase chain reaction and western blot. In addition, the protein expression of Rabl3 was examined in 162 cases of hepatocellular carcinoma by immunohistochemistry. Rabl3 in hepatocellular carcinoma cell lines was elevated at both messenger RNA and protein levels, and the Rabl3 protein was significantly upregulated by upto 3.3-fold in hepatocellular carcinoma compared with the paired normal hepatic tissues. Immunohistochemical analysis revealed that overexpressions of Rabl3 were 80.2% in hepatocellular carcinoma. Rabl3 is expressed at significantly higher rates in hepatocellular carcinoma compared with adjacent normal hepatic tissue (p < 0.01). Statistical analysis suggested the upregulation of Rabl3 was significantly associated with lymph node metastasis, tumor thrombus of the portal vein, and advanced clinical stage (p < 0.05). Furthermore, we found that overexpression of Rabl3 in hepatocellular carcinoma cells could significantly enhance cell proliferation and growth ability. Conversely, silencing Rabl3 by small hairpin RNA interference caused an inhibition of cell proliferation and growth. Our studies suggest that the Rabl3 is a valuable marker of hepatocellular carcinoma progression and that the overexpression of Rabl3 plays an important role in the development and pathogenesis of hepatocellular carcinoma.